THE INFLUENCE OF NORMATIVE COMMITMENT AND INTRINSIC MOTIVATION ON IN-ROLE BEHAVIOR AT CV. XYZ CIREBON - Purnomo, Yulio; Purnama, Erlan Angga; Burhan, Nurul (International Journal of Social Service and Research, 2024)
It is still found that there are employees who are less able to work professionally, such as attendance who are always late or do not come to work, there are still employees who are late to attend, and leave their work during break time beyond the specified time. The purpose of this study, to analyze the effect of Normative Commitment and intrinsic motivation on In-Role Behavior at CV. Xyz Cirebon, The type of research used is quantitative, a population of 228 employees with a sample of 146 respondents, this study states that there is a positive and significant effect of normative commitment variables and intrinsic motivation on in-role behavior. Normative commitment has a significant effect on in-role behavior, meaning that the better the normative commitment that exists in employees, the better the in-role behavior. intrinsic motivation has a significant effect on in-role behavior, meaning that the better the intrinsic motivation that exists in employees, the better the in-role behavior. normative commitment and intrinsic motivation have a significant effect on in-role behavior.